Energy balance measurements in an urban park in tropical city Delhi (India) - DAS, Yashvant; PADMANABHAMURTY, B. (Contributions to Geophysics and Geodesy, 2021)
Energy balance measurements were carried out in an urban vegetated area of Delhi. These measurements were made on several days during winter (November, December, January, February) and summer (April, May, June) of 1998 and 1999, respectively. Net radiation (Q*) and soil heat flux (G) were directly measured. Sensible heat flux (H) and latent heat flux (LE) were calculated from Bulk-aerodynamic approach and results are presented based on the analysis of energy balance components. Diurnal pattern of Q* shows pronounced variation indicating higher values during summers as compared to winters. Q* reached as high as 327.43 W/m2 during midday hours of summer 1999, whereas, it was about 100 W/m2 during winter 1998. Q* dissipated by 38% and 62% by H and LE during winter 1998, and the apportionment of H and LE accounted for about 34% and 51%, respectively during 1999. Nevertheless, 60% and 54% of Q* is utilized in heating the air of the lower atmosphere, compared to the 23% and 27% of Q* that is expended in evaporation in summer 1998 and 1999, respectively. On an average for all the seasons, daily total sum of energy fluxes is higher than net radiation by about 12.55 W/m2 indicating the deficit of energy during the study period. Probably, diurnal variation and seasonal differences in energy balance components are due to the nature of the substratum, plant phenology and local conditions which influence the energy partitioning. The calculated Bowen ratio and normalized energy balance components, when compared with other sites, support the hypothesis that the present study site is similar to the rural/vegetated area during winter season, but to an urban site during summer season. However, as there was no surplus of energy the area acts as a heat sink in both the seasons.